2015
DOI: 10.1002/ardp.201500037
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis, Antimicrobial, Antiquorum‐Sensing, and Cytotoxic Activities of New Series of Isoindoline‐1,3‐dione, Pyrazolo[5,1‐a]isoindole, and Pyridine Derivatives

Abstract: New series of isoindoline-1,3-diones 2-9, pyrazolo[5,1-a]isoindoles 10-14, and pyridines 16-18 were synthesized. Twenty of the synthesized compounds were screened for their antibacterial activity against S. aureus, B. cereus, and E. coli. Compound 5 was proved to be the most active member in this study, showing the highest antibacterial activity against the three selected microorganisms. The antifungal activity of these compounds was also tested against C. albicans and A. flavus 3375. Compounds 4, 5, 8, and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…It has been reported that the phthalimide moiety is a very important biologically active pharmacophore . Antimicrobial properties of phthalimide derivatives were reported . Compounds IV and V (Figure ) exhibited high antimicrobial activities against the tested microorganisms .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported that the phthalimide moiety is a very important biologically active pharmacophore . Antimicrobial properties of phthalimide derivatives were reported . Compounds IV and V (Figure ) exhibited high antimicrobial activities against the tested microorganisms .…”
Section: Introductionmentioning
confidence: 92%
“…Antimicrobial properties of phthalimide derivatives were reported . Compounds IV and V (Figure ) exhibited high antimicrobial activities against the tested microorganisms . Isoindole‐1,3‐dione is a building unit in antitumor, antiangiogenic as well as immunomodulatory drug candidates .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the antimicrobial screening of the compounds and extracts, their anti-pathogenic potential was checked by examining their antiquorum-sensing activity against Chromobacterium violaceum in LB agar medium as described previously (El-Gohary and Shaaban [12].…”
Section: Antiquorum-sensing Activitymentioning
confidence: 99%
“…A widespread and diversity of nitrogen heterocyclic molecules have been prepared and applied in the fields of medicinal, agro and combinatorial chemistry . Pyridines and their derivatives are a significant class of heterocyclic molecules which reveals a wide variety of promising biological activities such as anticancer, anti‐Inflammatory, antimalarial, anti‐oxidant, anti‐mycobacterial, antiviral, anti‐leishmanial, anti‐microbial, anti‐tubercular, anti‐proliferative and anti‐ulcer agents . Due to their feasible and scientific importance, various methods have been described in the literature for the preparation of several pyridine moieties.…”
Section: Introductionmentioning
confidence: 99%